Break Point - Klepikov, Milan D. (Iluminace, 2001)
The author returns to the turning points in the history of cinema that, in his opinion, influenced the further development of cinema. These are not only events, but also some filmmakers and their works.
Keywords: film history; film aesthetics; sound in film; black and white film; colour film